PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE (TPS) UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS IV MI AL-MUHSININ RIMBA MELINTANG - Rusita '; Otang Kurniaman; zairul Antosa (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The phenomenon of learning outcomes Social Sciences (IPS) grade 4 (four) MI Al Muhsinin Woods Crossing on material development of production technology still has not been done well. This fact is evident from Deuteronomy Days Before Cycle found students who did not complete as many 11orang (55.00%), while the number of students who completed as many as 9 people (45.00%) with an average grade 59.50 and Criteria for completeness Minimal specified school is 70.00. The purpose of this study improve the learning process in an effort to improve the results of social studies in grade IV MI Al-Muhsinin Rimba Melintang with the implementation of cooperative learning model type Think Pair Share (TPS). While the expected benefits in the implementation of cooperative learning model type Think Pair Share (TPS) to enhance the knowledge shaping the character of the students so that the ability to think, speak with IPS good in accordance with the standards of the national curriculum and also can be a reference for future researchers as reference material as well as an addition to insights for teachers MI / elementary school. The method used in this research is the Classroom Action Research (PTK) as the second cycle was conducted in April 2016 in MI Al Muhsinin Rimba Melintang. At each cycle performed two (2) meetings of learning and 1 (one) meetings for the Daily Deuteronomy done, then do the reflection to determine the next treatment. Based on the analysis of the research with the implementation of cooperative learning model Think Pair Share (TPS) preliminary data result of learning or Pre-cycle value of the average grade 59.50 with the percentage of completeness 45.00%, the first cycle increased to the value of the average grade 69.25 or the percentage of completeness 60.00% , on the second cycle increased the acquisition value of the average grade 75.50 with a percentage of 85.00% completeness. The conclusion from this study can improve learning outcomes IPS on the material development of production technology in class IV MI Al-Muhsinin Rimba Melintang. Key Word : Type Think Pair Share ( TPS ), Learning Outcomes IPS.